PENGARUH KINERJA GURU PRODUKTIF TERHADAP MINAT BELAJAR DAN KREATIVITAS SISWA PROGRAM KEAHLIAN TATA BUSANA DI SMK NEGERI 2 GOWA - Devi Darnita; Muhammad Andi Idkhan; Aisyah (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2022)
The purpose of this study was to discover the level of productive teacher’s performance, level of learning interest, and level of creativity as well as the influence of productive teacher’s performance on learning interest, and the influence of productive teacher’s performance on students’ creativity in Fashion Design Program at SMKN 2 Gowa in academic year of 2020/2021. This type of research is quantitative research, and the sampling technique used is the proportional cluster random sampling technique with a sample of 64 respondents. Methods of data collection employed observation, documentation, and questionnaires. The results show that 56.3% of teacher's performance is in high category, 68,8% of students is in medium level of learning interest, and 57,8% of students is in medium level of creativity. Based on the results of the study, partially the teacher's performance has a significant influence on learning interest with a percentage of 28.2%, while the teacher's performance has no influence on students' creativity.